Educational Policy Frameworks for Children with Chronic Diseases: A Cross-National Comparative Study - Defa Rahmatun Nisaa; Iman Subasman; Ade Aspandi; Dede Jajat; Muhammad Ridwan; Didi Rusmidi; Kiki Mustaqimah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Ensuring equitable access to education for children with chronic diseases remains a significant policy challenge, as prolonged medical treatment often disrupts learning continuity and social participation. This study aims to comparatively examine educational policies supporting children with chronic diseases in the United States, the United Kingdom, Finland, Australia, Japan, South Korea, and Indonesia. Employing a comparative policy analysis approach, the study analyzes national policy documents, international reports, and relevant scholarly literature to assess legal protection, hospital-based education, homebound learning, digital learning, psychosocial support, and cross-sector collaboration. The findings indicate that countries with comprehensive legal frameworks and well-established inclusive education systems provide more effective educational support through integrated services and flexible learning models. In contrast, Indonesia continues to face regulatory, institutional, and implementation challenges. The study concludes that strengthening legal protection, expanding hospital schooling, integrating educational technology, and enhancing collaboration between education and health sectors are essential to achieving inclusive and sustainable education for children with chronic diseases.